Business Process Reengineering for Red Onion E-Commerce System - Muhammad Noufal Baihaqi; Candra Irawan; Farrikh Alzami; Mila Sartika; Sri Handayani; Jumanto; Rindra Yusianto; Pulung Nurtantyo Andono (Universitas Medan Area, 2023)
Agriculture is a source of income for the country. One of the most promising agricultural commodities is shallots. Shallots are always found in every traditional market, traditional markets are one of the connecting places between buyers and sellers of shallots to carry out buying and selling activities of shallots. Onion buying and selling activities carried out in traditional markets are still conventional in this case, such as payment processing activities that still use cash, then in traditional markets the price of shallots is still not fixed, aka buyers can still haggle, so these two things are quite time-consuming and personnel in business process activities of shallot sales transactions. For this reason, here the author has the goal of doing business process reengineering to make the business process of buying and selling shallots in traditional markets more effective and efficient. By using the business process reengineering method, shallot transaction activities can be carried out using an e-commerce system, where the aim of this e-commerce system is to produce faster times for shallot transaction activities, process trimming, and reduce human resources in previous business process activities. as well as reducing costs. Thus, it is hoped that e-commerce can make the business process of buying and selling shallots between consumers and shallot traders more effective and efficient.